Morphological and molecular description of a new genus and species of black coral (Cnidaria: Anthozoa: Hexacorallia: Antipatharia: Antipathidae: Blastopathes) from Papua New Guinea - Horowitz, Jeremy; Brugler, Mercer R.; Bridge, Tom C.l.; Cowman, Peter F. (Zootaxa, 2020)
Blastopathes medusa gen. nov., sp. nov., is described from Kimbe Bay, Papua New Guinea, based on morphological and molecular data. Blastopathes, assigned to the Antipathidae, is a large, mythology-inspiring black coral characterized by clusters of elongate stem-like branches that extend out at their base and then curve upward. Colonies are not pinnulate and contain single branches, which could represent new branch cluster formations. Morphological and molecular (mitochondrial DNA and targeted capture of nuclear loci) evidence supporting the establishment of a new genus is discussed. This is the first study to utilize the target capture of ultraconserved elements (UCEs) and exonic loci to elucidate phylogenetic relationships among black corals and to identify and place a new genus and species.